Terrorism and Regional Security: The Challenges of Insurgency in the Sahel - Minka, Eleanor Salka; Opeyeoluwa, Rotimi Olajide (Àgídìgbo: ABUAD Journal of the Humanities, 2023)
This paper examines the incidences of terrorism in the Sahel region of Africa and its impact on regional security. The study suggests that terrorism festering in the Sahel is a product of bad governance and the inability of the states within the sphere of influence to exert the needed political will and corresponding action to nip in the bud the slip further down of insecurity. The study also posits that terrorism is a major hindrance to development. Using the Regional Security Complex Theory as a theoretical framework for analysis, the paper tries to explain how despondency results when regional intervention are not implemented. The paper recommends an overhaul of broader regional intervention as a matter of urgency, especially where state cannot tackle the security implications. The data used for this paper were gathered through secondary sources. These sources are textbooks, journal publications, newspapers, magazines and internet sources.